1993
DOI: 10.1111/j.2044-8279.1993.tb01045.x
|View full text |Cite
|
Sign up to set email alerts
|

Constructive response to failure in music: the role of attribution feedback and classroom goal structure

Abstract: Within the past decade, researchers have made significant progress in understanding how and why students are motivated to learn. Little research, however, has examined motivation within music classrooms, despite indications that motivational responses to music and related arts classes may differ significantly from responses obtained in other school content areas. In the present study, the effects of attribution feedback for failure (ability, effort, strategy) on behavioural and affective responses to failure i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

1995
1995
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 32 publications
0
10
0
Order By: Relevance
“…Considering the effect of attributing success or failure to the use of particular learning strategies, Vispoel and Austin (1993) found that students who explained their failure in relation to using poor learning strategies, or to making insuf cient effort, anticipated improving their performance, effort and strategy use in the future. Where failure was explained by lack of effort, students were likely to try harder in the future but not necessarily to improve their learning strategies.…”
Section: The Characteristics Of the Individual Learnermentioning
confidence: 98%
“…Considering the effect of attributing success or failure to the use of particular learning strategies, Vispoel and Austin (1993) found that students who explained their failure in relation to using poor learning strategies, or to making insuf cient effort, anticipated improving their performance, effort and strategy use in the future. Where failure was explained by lack of effort, students were likely to try harder in the future but not necessarily to improve their learning strategies.…”
Section: The Characteristics Of the Individual Learnermentioning
confidence: 98%
“…To sustain motivation, appropriate attribution strategies to explain success and failure need to be adopted. Most effective are those which focus on effort, practice and strategy use (Asmus, 1986a(Asmus, , 1986bMcPherson & McCormick, 1999;Vispoel & Austin, 1993). Overall, in music, attributions tend to be made regarding effort, musical background, classroom environment, musical ability and love of music (Arnold, 1997;Asmus, 1986aAsmus, , 1986bAsmus, , 1989Legette, 1998).…”
Section: Acquiring Effective Approaches To Learning Musicmentioning
confidence: 99%
“…Of course, a parent's beliefs about a child's putative talents can affect parental behaviours; hence such beliefs may indirectly affect a child's performance (e.g., Brophy & Good 1973). As noted in section 1, it is also true that selfbeliefs can predict future performance (Dweck 1986;Sloboda et al 1994a;Vispoel & Austin 1993). However, the question at issue is whether talent as such, as distinct from an individuals' beliefs about its presence, influences a child's attainments.…”
Section: Criticisms and Counterargumentsmentioning
confidence: 99%